Counterterrorism in the Southern American Cone - Tadeu Morato Maciel; Vinícius Armele; Mariana da Gama Janot; Karime Ahmad Borraschi Cheaito (Revista Conjuntura Austral)
Historically, there has been a lack of institutionalized cooperative efforts within the Union of South American Nations (UNASUR) to address terrorism, especially following its process of disintegration that began in 2018. However, is there a common "guiding line" between certain countries? This article examines South American responses to counterterrorism, with a particular focus on the Southern Cone, specifically Argentina, Brazil, and Chile. We argue that Critical Security Studies related to global security frameworks and Critical Terrorism Studies enable us to identify similarities in regional counterterrorism practices. Our analytical lens is focused on the counterterrorism legislation of these countries, highlighting the processes of mobilization and implementation of these laws. Through this approach, we aim to understand the perceptions and constructions surrounding terrorism and counterterrorism in each context. Methodologically, we propose a comparative historical analysis of responses to terrorism in the region after September 11, 2001. We conclude that the exercise of counterterrorism in these nations is driven by a confluence of internal security imperatives, financial considerations, and broader global security concerns. Thus, while cooperative efforts in forums such as UNASUR have been limited, there are elements of synergy in antiterrorism and counterterrorism legislation and practices.